Salicylic Acid in Wine as a Therapeutic Agent in Cardiovascular Disease - D.P. van Velden; H.K.L. Hundt (South African Family Practice)
Epidemiological evidence consistently links moderate wine consumption with reduced mortality, mostly due to reduced incidence of cardiovascular disease. Recent scientific reports indicating that a diet rich in fruit and vegetables, together with moderate amounts of alcohol, but more specific red wine in moderation, is protective against various degenerative diseases, created a renewed interest in the consumption of grapes and wine as part of a healthy diet and lifestyle.